Estudio comparativo sobre las herramientas de business intelligence: power bi y oracle bi - Villafuerte Rodríguez, Michael Omar (2022)
Business Intelligence (BI) tools help managers draw conclusions from the analysis of large amounts of informative data and make decisions with a better understanding of the real state of the company. Continuous improvement processes require accurate historical information. The creation of knowledge through the use of BI tools helps organizations to make future decisions with greater accuracy, however, there are various software in the market that must be selected depending on the nature of the company, the budget allocated to technology, etc. In the tools to compare we will realize that there is data integrity, as well as performance management applications which will help improve the company's performance. In this case study the BI Power and Oracle BI tools are analyzed based on literature research and information provided by the manufacturer, since the software cannot be installed because there is no computer that meets the hardware requirements, we start reviewing the manufacturer's documentation and features. included in reports such as Gartner Inc. a US based ICT consulting and research company. After analyzing the reports, it can be concluded that Power is preferred for response times, price, among other features.